Identifikasi Ikan Hiu Yang Tertangkap di Perairan Barat Aceh dan Status Konservasinya - Sutio Sutio; Maria Ulfah; Rizwan Rizwan (Universitas Syiah Kuala, 2018)
ABSTRACT Sharks are the top predators in the sea, and if the top predators disappear from a waters then the ecological balance in the waters will be disrupted. Ecologically, sharks play an important role in the food chain and as a balancer for ecosystem in the oceans. This study aims to determine the type of shark based on species located in the waters of West Aceh and the conservation status of shark species caught by the fishermen. The research was conducted in Rigaih fishing port (Aceh Jaya) and Ujong Baroh fishing port (West Aceh ) which is border by the Indian Ocean and has a high diversity in term of the biota. Sampling was conducted for 3 months, starting from February 2017 to April 2017. The method used was a survey with the identification of shark done by Rapid Assement (rapid estimation). Based on the results of the study found as many as 258 individuals consisting of 7 families, 9 genera and 11 species. From the shark data, there are several species included in the IUCN red list, is 1 species belonging to the EN (threatened) category of Sphyrna lewini species known as hammerhead sharks where the species are threatened and extinct, 2 species into VU ) species of Pelopicus or rat shark Alopias pelagicus or Squalus megalops or bottle sharks, where the category of this species is feared to have a high risk of extinction in the species, including the list of Appendix II CITES, then 4 species included in NT (almost threatened), and 3 other species in the category of Data Deficient.Keyword: Shark, Identification, CITES, IUCN Red List, West Aceh Sea ABSTRAK Hiu merupakan top predator di suatu kawasan perairan, dan apabila hilangnya top predator dari suatu perairan maka keseimbangan ekologi dalam perairan akan terganggu.Secara ekologi, hiu memainkan peran yang penting dalam rantai makanan dan merupakan penyeimbang ekosistem di lautan. Penelitian ini bertujuan untuk mengetahui jenis hiu berdasarkan spesies yang berada di perairan Barat Aceh dan status konservasi spesies hiu yang tertangkap.Penelitian dilakukan di TPI Rigaih (Aceh Jaya) dan TPI Ujong Baroh (Aceh Barat) yang berbatasan dengan samudra hindia dimana memiliki tingkat keanekaragaman yang tinggi akan biota lautnya. Samplingdilakukan selama 3 bulan, dimulai dari bulan Februari 2017 hingga April 2017. Metode yang digunakan adalah survei dengan identifikasi hiu yang dilakukan secara Rapid Assement (pendugaan secara cepat). Berdasarkan hasil penelitian ditemukan sebanyak 258 individu yang terdiri dari 7 famili, 9 genus dan 11 spesies. Dari data hiu tersebut terdapat beberapa yang termasuk kedalam IUCN red list, yaitu 1 spesies masuk dalam kategori EN (terancam) yaitu spesies Sphyrna lewiniatau yang dikenal dengan hiu martildimana spesies tersebut keberadaannya terancam dan memiliki resiko kepunahan, 2 spesies masuk kedalam VU (rawan) yaitu spesies Alopias pelagicus atau hiu tikus dan Squalus megalopsatau hiu botol, dimana kategori spesies ini dikhawatirkan memiliki resiko yang tinggi terhadap kepunahan dialam, spesies ini termasuk kedalam daftarAppendiks II CITES, kemudian 4 spesies termasuk dalam NT (hampir terancam), dan 3 spesieslainnya dalam kategori Minim informasi (Data deficient).Kata kunci : Hiu, Identifikasi, CITES, IUCN red list, Perairan Barat Aceh .